Lab sessions in VISIR laboratories - Gustavsson, Ingvar (2016)
Experimental activities with real components are an essential part of all courses including or devoted to electrical and electronic circuits theory and practice. The knowledge triangle composed of hand-written exercises, simulations and traditional lab experiments has been enriched with the possibility for students to conduct real experiments over the Internet, using remote labs. This tutorial is devoted to one such remote lab named Virtual Instrument Systems in Reality (VISIR). The Global Online Laboratory Consortium (GOLC) elected VISIR as the best remote controlled laboratory in the world, at the first time this distinction was awarded. At the end of this tutorial, attendees are expected to know what is VISIR, what can (not) be done with it, who is currently using it, and how can one integrate it in a given course curriculum.